2013
DOI: 10.1111/j.1464-410x.2012.11721.x
|View full text |Cite
|
Sign up to set email alerts
|

The true risk of blood transfusion after nephrectomy for renal masses: a population‐based study

Abstract: What's known on the subject? and What does the study add?• There is a paucity of population-based analyses of expected outcomes after renal surgery for kidney cancer. Reported blood transfusion rates after nephrectomy show considerable variability, probably as a result of the referral patterns that influence reports from tertiary academic medical centres.• With emerging data on the inferior outcomes in patients undergoing allogeneic blood transfusion, we aimed to evaluate the patient, surgeon and hospital fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…The reported rates of PBT with nephrectomy have varied considerably and probably also reflect disparate populations studied, as well as a lack of standardised criteria for transfusion. Notably, a recent population‐based study of 10 902 nephrectomies reported a transfusion rate of 18.1% , similar to our experience here (21%). Contributing to our rate of PBT, may also be the tertiary referral nature of our practice, as 46% of those who received a PBT had pT3/4 disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported rates of PBT with nephrectomy have varied considerably and probably also reflect disparate populations studied, as well as a lack of standardised criteria for transfusion. Notably, a recent population‐based study of 10 902 nephrectomies reported a transfusion rate of 18.1% , similar to our experience here (21%). Contributing to our rate of PBT, may also be the tertiary referral nature of our practice, as 46% of those who received a PBT had pT3/4 disease.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, nephrectomy (including partial and radical) has been associated with a perioperative blood transfusion (PBT) rate ranging from 3.5% to 18.1% . Previous reports have shown an increased risk of cancer recurrence in patients receiving a PBT after surgery for colon, hepatic and oesophageal malignancies .…”
Section: Introductionmentioning
confidence: 99%
“…106,111 The Charlson comorbidity index has also been associated with mortality in the setting of kidney cancer patients 112 , as well as with blood transfusion rates in patients undergoing nephrectomy for renal masses. 113 …”
Section: Charlson-deyo Comorbidity Scorementioning
confidence: 99%
“…For over 10,000 patients recorded on a Canadian discharge database, an overall transfusion rate of 18.1% was reported. 5 Multivariate logistic regression showed an association between age, Charlson co-morbidity index, procedure type, surgeon and hospital volume, and need for blood transfusion. Our study has some limitations.…”
Section: Discussionmentioning
confidence: 98%
“…4 The blood transfusion rate from a national database was 18.1%. 5 The British Association of Urological Surgeons (BAUS) nephrectomy database was launched in 2001 to collect surgeon reported outcome data. Data submission was voluntary.…”
mentioning
confidence: 99%